165 Improving care of patients with terminal agitation (ta) at end of life at leeds teaching hospitals nhs trust. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Iwaniszak, Claire; Rees, Elizabeth; Meal, Rachael; Winfield, Anna; Pattison, Craig; Hodge, Katie; Kite, Suzanne
Abstract : Aim: Our multidisciplinary team quality improvement project aimed to ensure that all dying patients who experience TA have an effective individualised plan of care on an acute stroke ward (L21) within a tertiary centre. Background: Leeds Teaching Hospitals was selected to be one of 10 hospitals to be part of the national 'Building on the Best Programme' in conjunction with Hospice UK, Macmillan, NHSE and NHSI. This was to build on what was already being achieved by hospitals to improve the quality of end of life care (EOLC). Often improvement work focuses on the management of pain and we wanted to focus on improving the care of patients with TA, a symptom found in up to 90% of dying patients, but not always focused on. Methods: This work was led by the Palliative Care team in conjunction with the frontline team on L21. A driver diagram was produced to identify key areas of focus (FIG 1). Interventions included ward-based role modelling of expert care of the dying; (this included the recognition, assessment, care planning and evaluation of interventions for patients experiencing TA), ward-based teaching, display and presentation of improvement data and discussion of dying patients in safety huddles. Run charts were created for these initiatives, with baseline data pre-intervention and on-going data collection during the testing, implementation and sustainability phases. All interventions were developed following identification of gaps in care delivery/evaluation. Results: Run charts (FIG 2–4) demonstrated statistically significant improvements in the rate of assessment, reassessment and evaluation of terminal agitation (p<0.05). Routine review and dissemination of data with the frontline teams in these initiatives enhanced collaborative engagement, motivation and success. Conclusion: Through collaborative working and ward-based role modelling we have demonstrated it is possible to improve the overall management of this challenging symptom in terminal care.